Opportunity for mitigating soil loss by water erosion in cropland through crop switching and improved management in China - Keke Li; Zhanhang Zhou; Zhen Wang; Yi Zeng; Klaus Hubacek; Pasquale Borrelli; Cai Li; Wenting Zhang; Zhongci Deng; Jingyu Wang; Zhihua Shi (Geography and Sustainability)
Cropland is persistently affected by soil loss by water erosion in China, which causes economic loss and threatens soil health. Integrating crop switching and improved management provides a promising strategy for controlling soil loss by water erosion in cropland and promoting sustainable agriculture. However, optimizing crop composition with fewer inputs involves balancing agricultural resource use with environmental costs. Aiming to explore the potential of crop switching as a strategy for mitigating soil erosion in cropland, we develop a spatial optimization model that redistributes the sown areas of different crops in each prefecture-level city based on existing resource availability. Our findings gained from our simulations show that crop switching in China alone can reduce total soil erosion in cropland by an estimated 13 %. Furthermore, combining crop switching with improved agricultural management practices can further reduce soil erosion in cropland by an estimated 25 %. Cereals including maize, wheat, and rice demonstrate significant potential for reducing soil erosion in cropland. Shifting major maize-producing areas northward could result in a substantial decrease in soil erosion, ranging from 10 % to 19 % of historical soil erosion in cropland. These results offer implications for formulating regional strategy in mitigating soil erosion challenges in China while maximizing the benefits from existing agricultural resource.